Exploring the Combination of Subtitling and Revoicing Tasks: A Proposal for Maximising Learning Opportunities in the Italian Language Classroom - BELTRAMELLO, ANASTASIA (International Journal of Language, Translation and Intercultural Communication, 2019)
Research has proven that audiovisual translation as an instructional tool is certainly beneficial to the enhancement of language skills, mainly listening, reading and writing. The relationship between the pragmatics of audiovisual (AV) material and the way they are learned, is still a topic that requires more investigation. In this study, clips form an Italian TV series are exploited as context-rich scaffolding on which students can build up vocabulary and develop an awareness of L2 pragmatics. This article presents an innovative didactic methodology that capitalised on the linguistic richness of audiovisual texts and sees in subtitling and revoicing tasks a great didactic potential that provides students with numerous opportunities for learning vocabulary and L2 pragmatic. In the course proposed, exposure to AV input is integrated with subtitling and revoicing tasks as well as with multimodal analysis of the video clips in order to maximise learning opportunities in the FL classroom.